Propagação in vitro de barueiro (Dipteryx alata Vog.) - Araruna, Elequisandra da Costa (2015)
Savannah is the second biome in biodiversity in Brazil, presenting great vegetation endemism. Dipteryx alata Vog. (Fabaceae), native from this biome, is an economically important species, with an incipient market due to the lack of commercial plantations. This highlights the need to develop and provide the basis for the domestication of this species. Thus, this study determined the best conditions for in vitro establishment, multiplication, elongation and rooting of stem tips of D. alata plantlets grown vitro. Two culture media (MS and WPM) were evaluated in different salt concentrations (25, 50, 75 and 100%) for plantlet establishment. Four concentrations of 6– Benzylaminopurine (BAP) (0, 1, 2, 3 and 4 mg L-1) amended with 0.25 mg L-1 naphthalene-acetic acid (NAA) were studied for multiplication. Simultaneous elongation and rooting were studied with four concentrations of NAA (0, 1, 2, 3 and 4 mg L-1) together with 0.5 mg L-1 IBA. The variables analyzed were: shoot length (CPA), root length (CP), fresh matter (MF), dry matter (MSC), stem diameter (DC) and number of leaves (NF), 120 days after inoculation, with the exception of number of shoots, which was evaluated in the multiplication stage only. The medium MS at the original salt concentration (100%) was effective for the in vitro establishment of E. alata, resulting in greater root length (27.65 cm) and number of leaves per plantlet (26.0). The concentration of 4 mg L-1 BAP was the best one for multiplication; however, greater concentrations can boost multiplication. The effect of NAA and IBA were noticeable on in vitro elongation and rooting, with best CPA (3.14 cm) and CR (15.84 cm). Therefore, it is possible to state that the medium MS increases the success probability of in vitro establishment of stem tips of Dipteryx alata. NAA concentrations below 3 mg L-1 were favorable for in vitro development of the species, with essential characteristics for acclimatization success|.